Exploring the Relationship Between Social Commerce Features and Consumers’ Repurchase Intentions: The Mediating Role of Perceived Value - Guo, Jinyuan; Li, Lei (Frontiers in Psychology, 2022)
Purpose- Although shopping through social commerce platforms is widely favored by consumers, the factors affecting consumers’ repurchase intention in the social commerce environment remain unclear. Therefore, we build a consumer repurchase decision model in the social commerce environment, analyze the influencing mechanism of social commerce features (interactivity, recommendations, feedback) on perceived value (utilitarian value, hedonic value) and consumers’ repurchase intention. Design/methodology/approach- Hypotheses are tested with structural equation modeling with applied to data collected via a survey of the respondents were consumers who had experienced shopping on WeChat. Findings- The empirical results found that social commerce features are positively related to the generation of perceived value, which in turn drives consumers to form repurchase intentions. We also found some mediating effects of perceived value. Research limitations/implications- This study has relied on a convenient sampling and this may limit the generalizability of the findings. Future research should employ broader and more random sampling techniques to re-validate and extend our findings. Originality/value- The study’s conclusions clarify the intrinsic influence mechanism of social commerce features on consumers’ perceived value and repurchase intentions. In addition, it can provide some theoretical guidance for future research and business.